Macroporous Hyaluronic Acid/Chitosan Polyelectrolyte Complex-Based Hydrogels Loaded with Hydroxyapatite Nanoparticles: Preparation, Characterization and In Vitro Evaluation - Maria G. Drozdova; Tatiana S. Demina; Ostap A. Dregval; Anna I. Gaidar; Elena R. Andreeva; Alexander N. Zelenetskii; Tatiana A. Akopova; Elena Markvicheva (Polysaccharides, 2022)
The aim of the study was to fabricate and characterize composite macroporous hydrogels based on a hyaluronic acid/chitosan (Hyal/Ch) polyelectrolyte complex (PEC) loaded with homogeneously distributed hydroxyapatite nanoparticles (nHAp), and to evaluate them in vitro using mouse fibroblasts (L929), osteoblast-like cells (HOS) and human mesenchymal stromal cells (hMSC). Hydrogel morphology as a function of the hydroxyapatite nanoparticle content was studied using scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM). The mean pore size in the Hyal/Ch hydrogel was 204 ± 25 μm. The entrapment of nHAp (1 and 5 wt. %) into the Hyal/Ch hydrogel led to a mean pore size decrease (94 ± 2 and 77 ± 9 μm, relatively). Swelling ratio and weight loss of the hydrogels in various aqueous media were found to increase with an enhancement of a medium ionic strength. Cell morphology and localization within the hydrogels was studied by CLSM. Cell viability depended upon the nHAp content and was evaluated by MTT-assay after 7 days of cultivation in the hydrogels. An increase of the hydroxyapatite nanoparticles loading in a range of 1–10 wt. % resulted in an enhancement of cell growth and proliferation for all hydrogels. Maximum cell viability was obtained in case of the Hyal/Ch/nHAp-10 sample (10 wt. % nHAp), while a minimal cell number was found for the Hyal/Ch/nHAp-1 hydrogel (1 wt. % nHAp). Thus, the proposed simple original technique and the design of PEC hydrogels could be promising for tissue engineering, in particular for bone tissue repair.